The Research of Clay Tobacco Pipes and Its Methodological Aspects - Žvirblys, Atas (Archaeologia Lituana, 2021)
Clay pipes are quite a common finding in the study of urban cultural strata, a dozen thousand fragments of them are counted in the collections of Lithuania museums. Nevertheless, the terminology of these of tobacco pipes is not yet quite settled in Lithuania, and archaeologists who investigate urban areas do not even have a methodical material published in Lithuanian. The article aims to distinguish and define the methodological aspects of the analysis of clay tobacco pipes dated from the first half of 17th century to 19th century, which would be suitable for the Lithuanian context. At the beginning of this article, the history of clay tobacco pipes research is analyzed in a methodological aspect, the links to the whole development of archaeology science are presented, and the current tendencies in the tobacco pipes researches are described. The other chapters focus on the matters of clay pipes terminology, methods of analysis, and dating. Considering the locally produced and imported pipes found in Lithuania, methodical matters of recording and describing these findings are analyzed, as well as possible interpretations of the collected data.
Keywords: clay tobacco pipes; one-piece pipes; composite pipes